Soil bacterial communities associated with marbled fruit in Citrus reticulata Blanco ‘Orah’ - Huang, Qichun; Wang, Nina; Liu, Jimin; Liao, Huihong; Zeng, Zhikang; Hu, Chengxiao; Wei, Chizhang; Tan, Songyue; Liu, Fuping; Li, Guoguo; Huang, Hongming; Chen, Dongkui; et al. (Frontiers in Plant Science, 2023)
Citrus reticulata Blanco 'Orah' is grown throughout southern China and provides enormous economic value. However, the agricultural industry has suffered substantial losses during recent years due to marbled fruit disease. The present study focuses on the soil bacterial communities associated with marbled fruit in 'Orah'. The agronomic traits and microbiomes of plants with normal and marbled fruit from three different orchards were compared. No significant differences were found in agronomic traits between the groups, except for higher fruit yields and higher quality of fruits in normal fruit group. Additionally, a total of 2,106,050 16S rRNA gene sequences were generated via the MiSeq platform. The alpha diversity index (including the Shannon and Simpson indices), Bray–Curtis similarity, and principal component analyses indicated no significant differences in microbiome diversity between normal and marbled fruit groups. For the healthy 'Orah', the most abundant associated phyla were Bacteroidetes, Firmicutes, and Proteobacteria. In comparison, Burkholderiaceae and Acidobacteria were the most abundant taxa with the marbled fruit group. In addition, the family Xanthomonadaceae and the genus Candidatus Nitrosotalea were prevalent with this group. Analysis using the Kyoto Encyclopedia of Genes and Genomes pathways showed that several pathways related to metabolism significantly differed between the groups. Thus, the present study provides valuable information regarding soil bacterial communities associated with marbled fruit in 'Orah'.